Pharmacokinetics and pharmacogenetics of sorafenib in patients with hepatocellular carcinoma: Implications for combination trials. (25th July 2020) - Díaz‐González, Álvaro; Sapena, Víctor; Boix, Loreto; Brunet, Mercè; Torres, Ferrán; LLarch, Neus; Samper, Esther; Millán, Olga; Corominas, Josep; Iserte, Gemma; Sanduzzi‐Zamparelli, Marco; da Fonseca, Leonardo G.; et al.
Abstract: Background & Aims: Sorafenib and lenvatinib are the first‐line treatments approved in hepatocellular carcinoma (HCC), but information is lacking about the relationships between their pharmacokinetics, patients pharmacogenetic profiles, adverse events (AE) and overall survival. We aimed to elucidate these relationships of tyrosine Kinase Inhibitors, such as sorafenib, in order to improve the design of trials testing it in combination with checkpoint inhibitors. Methods: We assessed the pharmacokinetics of sorafenib and its N‐oxide metabolite at day‐0, day‐7, day‐30, day‐60, day‐90, day‐120, day‐150 and day‐180 and nine single‐nucleotide polymorphisms (SNP) in five genes related to sorafenib metabolism/transport to identify the best point for starting the combination between tyrosine kinases and checkpoint inhibitors. Results: We prospectively included 49 patients (96% cirrhotic, 37% hepatitis‐C, 82% Child‐Pugh‐A and 59% BCLC‐C). Pharmacokinetic values peaked at day‐7 and progressively declined until day‐60. In the 16 patients without further dose modifications after day‐60, pharmacokinetic values remained stable through day‐180 (sorafenib P = .90; N‐oxide P = .93). Pharmacokinetic values were higher in patients with early dermatological adverse events and lower in patients with early diarrhoea. Sorafenib and N‐oxide pharmacokinetic values varied linearly with different alleles of MRP2*3972 . Conclusions: Sorafenib's pharmacokinetics is heterogeneous across HCC patients. This heterogeneity affects adverse events development and must be taken into account in setting the dose and timing of its combination with checkpoint inhibitors.